2017
DOI: 10.12693/aphyspola.131.1225
|View full text |Cite
|
Sign up to set email alerts
|

Scaling-Based Analysis and Modelling of Power Losses in Amorphous and Nanocrystalline Alloys

Abstract: The paper presents the scaling-based approach to analysis and modelling of power losses in Fe-based amorphous and nanocrystalline alloys. Production technology and properties of these alloys are briefly presented. For each sample, a family of measured loss curves are collapsed onto a single one using appropriate estimated scaling parameters. An interpretation of the fractional exponent is discussed. The scaling analysis is used in the modelling of power losses for the considered alloys. The results of power lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Such results are congruent with previous literature data [44,45]. It was previously shown that the domain structure would suffer certain transformations owing to the sample size, induction amplitude, as well as other conditions and/or parameters [45][46][47][48], leading to difficulties concerning total magnetic losses separation. To recall, power losses in soft magnetic materials are generated by hysteresis phenomenon and eddy currents, flowing in different scales as in the whole material volume, around moving domain walls or micro-currents related to the Barkhausen jumps.…”
Section: Resultssupporting
confidence: 92%
“…Such results are congruent with previous literature data [44,45]. It was previously shown that the domain structure would suffer certain transformations owing to the sample size, induction amplitude, as well as other conditions and/or parameters [45][46][47][48], leading to difficulties concerning total magnetic losses separation. To recall, power losses in soft magnetic materials are generated by hysteresis phenomenon and eddy currents, flowing in different scales as in the whole material volume, around moving domain walls or micro-currents related to the Barkhausen jumps.…”
Section: Resultssupporting
confidence: 92%
“…Moreover, magnetic losses in these composites will be analyzed using the scaling theory. The scaling theory has been previously applied in the magnetic losses analyzed for electrical steels, amorphous and nanocrystalline ribbons as well as magnetocaloric alloys [13][14][15], which provided interesting and useful results. The losses scaling should allow us to investigate multiscale behaviour of energy dissipation in Fe-polymer composites; to find universal relations between parameters; and finally to model magnetic composites for different Fe-grain size, excitation conditions or technological parameters.…”
Section: Resultsmentioning
confidence: 99%
“…The scaling analysis is also used in materials science, including the study of magnetic material properties such as power loss [30][31][32][33][34], coercivity [35][36][37], magnetic viscosity [38][39][40] or hysteresis loops [41][42][43][44][45].…”
Section: Scaling Analysis Of Magnetic Anisotropymentioning
confidence: 99%
“…In the previous studies, a scaling function was usually represented by Maclaurin series [30][31][32][33][34][35][36][37].…”
Section: Scaling Analysis Of Magnetic Anisotropymentioning
confidence: 99%